Guidelines for Writing a Book Review: Through the Lens of the First-Year Doctoral Student Experience - Orynbassarova, Dilara (NUGSE Research in Education, 2(1), 2017)
Writing a critical book review is an integral part of the scholarly development process of any emerging researcher. The payoff of writing a book review is great, as it helps the emerging scholar to sharpen both writing and critical thinking skills, and understand the process of writing and editing a book. A critical review of the book may include a brief yet effective summary of the book; the relevance of the ideas today in general; a thorough analysis of the author’s main concepts and ideas, including the discussion about the authors’ main arguments, how and why the author has put the book together in such away, how well the author has supported ideas and facts; and discussion of the book’s strengths and weaknesses, which may include the overall content, organization, style and application to a certain context. Mentioning whether the author has achieved the stated purpose of the book is also important. For example, you may find this information in the preface or the introduction part of the book. My personal experience of writing a critical book review indicates that the process has three stages: before, during and after.
Keywords: book review; doctoral student experience